Visible-Light Photoredox Catalyzed Formation of Triarylethylenes Using a Low-Cost Photosensitizer - Daniel Álvarez-Gutiérrez; Paola Domínguez Domínguez; Raúl Pérez-Ruiz; David Díaz Díaz; M. Consuelo Jiménez (Photochem)
Visible-light photoredox catalysis using biacetyl (BA) as a low-cost photosensitizer enables the efficient formation of triarylethylenes (TAEs) via a Mizoroki–Heck-type coupling. The reaction proceeds efficiently in acetonitrile upon blue LED irradiation under anaerobic conditions. Alternatively, supramolecular viscoelastic gels have also been explored as reaction media, allowing the possibility of working under aerobic atmosphere. Mechanistic investigations by means of transient absorption spectroscopy and quenching experiments support a charge-separated intermediate pathway. Reaction quantum yield measurements further validate the efficiency of BA, demonstrating its potential as an alternative to transition-metal catalysts. Overall, this work presents a sustainable and scalable strategy for TAEs synthesis, integrating photoredox catalysis with soft material engineering. These findings pave the way for broader applications in green chemistry and functional materials.